Wall-Pressure Fluctuations of Modified Turbulent Boundary Layer with Riblets - Abdulbari, Hayder A.; Hassan D., Mahammed; Zulkefli, Yaacob; Wafaa, Kamil Mahmood (IJENS, 2016)
The experimental design incorporated to study the response of a turbulent pressure drop fluctuations to differently shaped longitudinal grooves, involved three conformations or structures being triangular, trapezoidal and spaced triangular grooves with height 800 m. The ratios of the groove height to groove space for triangular were: 1, 0.8, 0.6 and 0.4. Experiments were therefore performed at free stream velocity up to 0.44m/sec, which were corresponding to Reynolds number (Re)5.3×. The development of the obtained turbulent layerdownstream of the grooves was then compared with the results from the corresponding smooth-wall case. To conclude, the effect of the spaced triangular riblets on the turbulent characteristics seemed to be more pronounced than the effects of the triangular and trapezoidal riblets.